2012
DOI: 10.1016/j.jpain.2012.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Course and Impact of Insomnia Symptoms in Adolescents With and Without Chronic Pain

Abstract: and Perspective This study aimed to: 1) examine trajectories of insomnia symptoms in adolescents with chronic pain compared to their healthy peers, 2) evaluate psychological and behavioral risk factors for longitudinal insomnia symptoms, and 3) evaluate insomnia as a predictor of quality of life, activity limitations, and healthcare utilization over 12 months. Participants included 61 adolescents with chronic pain and 60 youth without chronic pain (12–18 years; 72% female). Questionnaires were completed at enr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
59
2
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(67 citation statements)
references
References 28 publications
5
59
2
1
Order By: Relevance
“…Before the study onset 76% of patients from the study group and 71% of patients from the control group reported significant sleep disturbances, scoring more than 10 points on the AIS scale. Numerous studies emphasise the widespread problem of sleep disturbances, in particular in patients with chronic somatic disorders [16]. Patients with painful sensorimotor polyneuropathy very often complain of sleep disturbances, which have been confirmed in the presented study.…”
Section: Prace Oryginalnesupporting
confidence: 81%
“…Before the study onset 76% of patients from the study group and 71% of patients from the control group reported significant sleep disturbances, scoring more than 10 points on the AIS scale. Numerous studies emphasise the widespread problem of sleep disturbances, in particular in patients with chronic somatic disorders [16]. Patients with painful sensorimotor polyneuropathy very often complain of sleep disturbances, which have been confirmed in the presented study.…”
Section: Prace Oryginalnesupporting
confidence: 81%
“…These may include financial analyses of the costs and benefits of addressing sleep in its own right and as part of the treatment of other health and mental health problems. While the implementation of sleep-related training programs would represent an economic investment, there is growing evidence that, given the profound impact of sleep on health and functioning, not treating sleep presents a substantial economic burden to the healthcare system (Daley et al, 2009;Kapur et al, 2002;Palermo, Law, Churchill, & Walker, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Participants were recruited from a variety of sources, including referrals from pediatric medical subspecialties, a health maintenance organization pharmacy database, ongoing psychological intervention trials, a hospital trauma registry, and community advertisements. Information regarding recruitment for several of these studies has been previously published (Holley et al, 2013; Law, Dufton, & Palermo, 2012; Murray et al, 2012; Palermo, Law, Churchill, & Walker, 2012; Palermo et al, 2011). …”
Section: Methodsmentioning
confidence: 99%